2020
DOI: 10.20473/bhsj.v3i1.19131
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Challenge Of Peritoneal Tuberculosis In Woman With Ascites

Abstract: Tuberculosis (TB) is a major health global issue including extrapulmonary tuberculosis (EPTB). The one of manifestation of EPTB is peritoneal TB that constitutes 2% from all cases of pulmonary TB around the world. The diagnosis of peritoneal TB is quite challenging because many cases have symptom that similar to other diseases and those often necessary need further specific examinations such as PCR, culture and radiologic examination. We reported a case report of peritoneal tuberculosis in woman with ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Previous studies indicates that an ADA level of >40 IU/L in ascitic fluid indicates the occurrence of peritoneal tuberculosis [ 8 ]. Furthermore, the utilization of GeneXpert MTB/RIF in ascitic fluid plays a vital role in promptly diagnosing peritoneal tuberculosis, enabling quick initiation of tuberculosis treatment and enhancing treatment efficacy [ 9 , 10 ]. The abdominal CT scan is also crucial for assessing the patient's peritoneal status [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicates that an ADA level of >40 IU/L in ascitic fluid indicates the occurrence of peritoneal tuberculosis [ 8 ]. Furthermore, the utilization of GeneXpert MTB/RIF in ascitic fluid plays a vital role in promptly diagnosing peritoneal tuberculosis, enabling quick initiation of tuberculosis treatment and enhancing treatment efficacy [ 9 , 10 ]. The abdominal CT scan is also crucial for assessing the patient's peritoneal status [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal tuberculosis treatment comprises ATD use, surgical intervention, and medication monitoring. After 4–6 weeks of ATD use, the majority of patients demonstrate clinical improvement in peritoneal tuberculosis [ 11 ]. If problems develop, such as excessive bleeding, blockage, perforation, and so on, surgery is required.…”
Section: Discussionmentioning
confidence: 99%
“…14 Adenosine deaminase (ADA) measurement is useful to evaluate patients with suspected PTB. 22 ADA levels of ascitic fluid 40 IU/L show excellent sensitivity, although the specificity is relatively low for the diagnosis of PTB. 22 A meta-analysis found that ADA had high sensitivity (100%) and specificity (97%) using cut-off of 36-40 U/L.…”
Section: Discussionmentioning
confidence: 99%
“…22 ADA levels of ascitic fluid 40 IU/L show excellent sensitivity, although the specificity is relatively low for the diagnosis of PTB. 22 A meta-analysis found that ADA had high sensitivity (100%) and specificity (97%) using cut-off of 36-40 U/L. 23 In cirrhosis patients, the sensitivity is only 30% due to poor humoral and T-cell response.…”
Section: Discussionmentioning
confidence: 99%